2017
DOI: 10.21705/mcbs.v1i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sRAGE and hsCRP as Markers of Cardiovascular Disease Risk Factors in Diabetic and Non-Diabetic Men with Central Obesity

Abstract: Background:Interaction between advanced glycation end product (AGE) and receptor for AGE (RAGE) triggers the escalation of inflammatory cytokine expressions. High-sensitivity C-reactive protein (hsCRP), an important inflammatory marker, has been reported to be modulated by soluble RAGE (sRAGE). However, the relationship between hsCRP and sRAGE in diabetes was not clearly described. Therefore present study was conducted to determine the relationship between sRAGE with hsCRP in men with central obese diabetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Some researchers have focused on the relationship between AGEs, circulating RAGE levels and hsCRP in different diseases. Interestingly, some authors postulated that low levels of sRAGE may promote the AGEs—RAGE interaction resulting in production of cytokines and, consequently, the increased serum level of CRP [37,38]. In the present study, this activation may be reflected by the positive correlation between CECs and hsCRP levels, which therefore suggests that systemic inflammation plays a significant role on endothelial damage in hypertensive patients.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Some researchers have focused on the relationship between AGEs, circulating RAGE levels and hsCRP in different diseases. Interestingly, some authors postulated that low levels of sRAGE may promote the AGEs—RAGE interaction resulting in production of cytokines and, consequently, the increased serum level of CRP [37,38]. In the present study, this activation may be reflected by the positive correlation between CECs and hsCRP levels, which therefore suggests that systemic inflammation plays a significant role on endothelial damage in hypertensive patients.…”
Section: Discussionsupporting
confidence: 50%
“…McNair and co-authors demonstrated lower sRAGE levels, while hsCRP and TNF-α concentrations were higher in patients with non-ST-segment elevation myocardial infraction compared to control group [37]. Hamuaty and co-workers found that the protective function of sRAGE reflected an inverse relationship between hsCRP and sRAGE in the early stages of diabetes [38]. In the present study, for the first time to our knowledge, we have demonstrated a significant and reversible association between sRAGE concentrations, AGEs/sRAGE ratio, and hsCRP concentrations in MH patients with medium level of hsCRP (1 mg/L ≤ hsCRP < 3 mg/L).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is one of metabolic diseases with hyperglycemia due to the abnormality of pancreatic β cell insulin secretion, insulin resistance or both. (1,2) According to the International Diabetes Federation (IDF) in 2019, there were 463 million adults, aged 20-79 years old, diagonised with DM, in the world. (3) This represented 9.3% of world's population in this age group.…”
Section: Introductionmentioning
confidence: 99%
“…Early identification was needed to deal with earlier prevention or delaying the disease to be started. (6)(7)(8)(9) Recent studies found variations in blood metabolite profiles before and after glucose loading (10)(11)(12) as well as in obese compared with lean individuals (13). What have been noticed from those studies is the differences in the quantity of some small molecules such as C3 and C5 acylcarnitines, glutamine and glutamate, and extra amino acids in both groups, suggest that individual risk and onset of T2DM can be predicted by the alteration of those plasma metabolite concentrations.…”
Section: Mechanisms Of Insulin Receptor Signalingmentioning
confidence: 99%